Automatização do processo de abastecimento de uréia através do controle de nível na produção de MDF - Ubaldo, Willian Antunes de Souza (2016)
The Urea Supply Process Automation project with Level Control in MDF Production relates the benefits of industrial automation, so that the reliability and determinism will be increases in a specific process for level control. Where the level control is made manually it’s possible improve the system precision and time of response by implementing automation. In a practical way the level control was analyzed, which the analogical sign is staggered through a Programmable Logic Control and represented by graphic ilustrations via SCADA system. For the resin level control two types of distance sensors has been considerate: ultrasonic and optic, both adjusted to emit a 4-20mA signal. The project analyses reasons for automate a manual system on a practical way to ensure that can be no measuring erros in resin suplly process.